Cloth hot stamping foil with heat storage function and preparation method of cloth hot stamping foil

By optimizing material selection and drying conditions, combining nanofiber layers and high-purity aluminum-plated layers, the shortcomings of existing hot stamped foils for fabrics in terms of bonding force, antistatic properties and thermal storage properties are solved, and a higher level of Performance and longer service life.

CN119388899APending Publication Date: 2025-02-07SUZHOU WONDERFUL NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411610682.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing hot stamped foil for fabrics has shortcomings in adhesion, antistatic properties and thermal storage properties, and cannot meet the needs of modern complex application scenarios.

Method used

By optimizing the material selection of the coloring layer and glue coating layer, adjusting the drying conditions, and adding nanofiber layers to the base layer, high-purity aluminum is used to form an aluminum-plated layer, combining environmentally friendly dyes and antistatic agents, improving the adhesion between the layers Junction force and antistatic properties.

Benefits of technology

It significantly improves the bonding, antistatic properties and heat storage properties of the hot stamped foil for fabrics, meets the needs of modern and diversified markets, extends the service life of the product, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119388899A_ABST
    Figure CN119388899A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat transfer films, in particular to a hot stamping foil with a heat storage function for cloth and a preparation method of the hot stamping foil. The invention relates to an anti-counterfeiting film which comprises a base layer, the top end of the base layer is provided with a release layer, the top end of the release layer is provided with an aluminized layer, the top end of the aluminized layer is provided with a coloring layer, the top end of the coloring layer is covered with a gluing layer, and the gluing layer adopts an acrylic resin binder. The coloring layer is obtained by drying a coloring agent, and the coloring agent comprises environment-friendly dye, an organic solvent, polyurethane resin and an accelerant. By optimizing the dosage of the coloring agent, the type of the resin binder and the production process, the binding power, the antistatic performance and the heat storage performance of the hot stamping foil for the heat storage functional cloth are comprehensively improved. Due to the improvement of the comprehensive performance, the product can better meet the modern diversified market requirements, and can be applied to daily clothes decoration, warm-keeping articles and application scenes related to electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat transfer films, in particular to a hot stamping foil for cloth with a heat storage function and a preparation method thereof. Background Art

[0002] The transfer film is an intermediate carrier, which exists on the transfer paper base or plastic base, carries the printed or printed pattern, and is used to transfer a layer of chemical elastic film onto the printed object. It is widely used in advertising, decoration, etc. According to the specific use, it can be divided into advertising heat transfer film, leather heat transfer film, gold and silver cardboard heat transfer film, textile heat transfer film, etc. In the field of hot stamping foil for heat storage functional fabrics, materials with multiple characteristics such as good adhesion, antistatic properties and heat storage properties are required. Traditional hot stamping foils may only focus on one aspect of performance and cannot meet the needs of modern complex application scenarios. For hot stamping foil for fabrics, if the electrostatic potential is too high, it will not only affect its appearance and neatness, but also may have adverse effects on the electronic equipment or human body to which it is applied. The quality of adhesion is directly related to the adhesion effect of hot stamping foil on fabrics. In daily use, washing or friction, if the adhesion is insufficient, the hot stamping foil is easy to fall off, affecting the service life and aesthetics of the product. At the same time, heat storage performance is of great significance in some special application scenarios, such as warm clothing, etc. Improving heat storage performance can increase the added value of products.

[0003] The adhesives used in some existing hot stamping foil material formulas may not work well with other ingredients, resulting in less than ideal adhesion between the layers. This reflects the problems that may exist in the prior art in terms of optimization of adhesion, such as unreasonable dosage of ingredients. In terms of antistatic performance, traditional antistatic agents may not be effective or may not fully function in a specific system, indicating that there is room for improvement in the selection and dosage optimization of antistatic agents in the prior art. As for heat storage performance, the structural design or composition of existing materials may not be conducive to heat storage. At the same time, due to unreasonable adjustment of production process conditions, the prior art has limitations in improving heat storage performance. Summary of the invention

[0004] The object of the present invention is to provide a hot stamping foil for cloth with heat storage function and a preparation method thereof, by optimizing the material selection of the coloring layer and the adhesive layer, optimizing the material and dosage selection of the colorant, and adjusting the drying conditions during preparation, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above-mentioned purpose, on the one hand, the present invention provides a hot stamping foil for cloth with heat storage function, including a base layer, a release layer is arranged on the top of the base layer, an aluminum-plated layer is arranged on the top of the release layer, a coloring layer is arranged on the top of the aluminum-plated layer, and the top of the coloring layer is covered with a glue coating layer.

[0006] As a further improvement of the present technical solution, the base layer is a composite layer of biaxially stretched polypropylene film and polyethylene film; at the same time, on the basis of the composite layer of biaxially stretched polyethylene film and polyethylene film, a nanofiber layer is added, and the nanofiber layer preferably uses polylactic acid nanofibers with high toughness and good air permeability, with the aim of further improving the strength and air permeability of the base layer, while enhancing the structural stability of the entire hot stamping foil.

[0007] As a further improvement of the present technical solution, the coating layer is a resin adhesive, and the resin adhesive is preferably an acrylic resin adhesive. Acrylic resin has good bonding properties, weather resistance and chemical stability. It can effectively bond the coloring layer to other layers in the coating layer of the hot stamping foil, and can adapt to different environmental conditions during the fabric hot stamping process to ensure the durability of the hot stamping effect.

[0008] As a further improvement of the technical solution, the coloring layer is obtained by drying a colorant, and the colorant includes the following components in parts by weight: 5-10 parts of an environmentally friendly dye, 10-20 parts of an organic solvent, 10-15 parts of a polyurethane resin, and 1-3 parts of an accelerator; Among them: the promoter is preferably an organic tin promoter (dibutyltin dilaurate). The organic tin promoter can accelerate the chemical reaction during the mixing process of the colorant, improve the compatibility between the components, so that the color of the coloring layer is more uniform and stable, and help to improve the adhesion between the coloring layer and the aluminum plating layer.

[0009] As a further improvement of the technical solution, the organic solvent is one or more combinations of butanone, cyclohexanone, and ethyl ester, and the environmentally friendly dye comprises the following components in parts by weight: 15-20 parts of acrylic resin, 1-3 parts of cellulose acetate resin, 10-20 parts of natural plant pigment, 50-70 parts of methyl isobutyl ketone, 1-5 parts of antistatic agent, 1-3 parts of wax powder, and 1-3 parts of sodium carbonate; Among them: the antistatic agent is preferably a polyethylene glycol type antistatic agent, which can effectively reduce the static electricity accumulation of the hot stamping foil during production and use, prevent dust adsorption, improve the quality and stability of the hot stamping foil, and also help to avoid the influence of static electricity on the hot stamping effect during the fabric hot stamping process.

[0010] In the present invention, there are entanglement of chain segments and intermolecular forces between the polyurethane resin in the coloring layer and the acrylic resin of the acrylic resin binder. This interaction helps to improve the bonding force between the coloring layer and the adhesive layer, making the structure of the entire hot stamping foil more stable; at the same time, the antistatic agent (polyethylene glycol type antistatic agent) in the coloring layer will affect the bonding effect. It can adjust the intermolecular forces to a certain extent and make the bonding more uniform.

[0011] On the other hand, the present invention provides a method for preparing the hot stamping foil for fabric with heat storage function as described in any one of the above, comprising the following steps: S1, selecting a composite film of biaxially oriented polypropylene film and polyethylene film as a base layer, coating a release agent on the surface of the base layer, and then sending it into an oven for drying and consolidation to form a release layer; S2. Heat the evaporation boat to 1500℃ in a vacuum environment, and continuously feed high-purity (99.999% purity) aluminum wire into the evaporation boat to make it sublimate into aluminum vapor, which then evenly adheres to the surface of the release layer to form an aluminum coating. When high-purity aluminum sublimates to form an aluminum coating, it can reduce the presence of impurities, thereby improving the conductivity, wear resistance and glossiness of the aluminum coating, making the hot stamping foil have a better visual effect after being stamped on the fabric, and performing better in some special fabric applications that require conductive properties. Secondly, the vacuum degree is 1×10 -3 -1×10 -4 Pa, a higher vacuum degree can reduce the interference of gas molecules on the movement of aluminum vapor molecules, allowing aluminum vapor to reach the surface of the release layer more smoothly and adhere; S3, putting environmentally friendly dyes, organic solvents, polyurethane resins, and accelerators into a stirring kettle, mixing and stirring to obtain a colorant, using an anilox roller to coat the colorant on the surface of the aluminum-plated layer, and then sending it into an oven for drying and consolidation to obtain a colored layer; since there are aluminum atoms on the surface of the aluminum-plated layer, during the process of colorant coating and drying and consolidation, the polyurethane resin in the colorant can undergo physical adsorption and chemical bonding with the aluminum surface, and the polar groups (such as amino groups, carboxyl groups, etc.) in the polyurethane resin can form coordination bonds or hydrogen bonds with aluminum atoms, which can enhance the adhesion between the colored layer and the aluminum-plated layer, making the colored layer more firmly attached to the aluminum-plated layer, and preventing the colored layer from falling off during use; and the accelerator in the colorant will affect this reaction, increase the activity of the polyurethane resin, and make it easier for it to react with the aluminum surface; S4, applying a resin binder to the surface of the coloring layer by an anilox roller, and then sending it into an oven for drying to obtain a coating layer; S5. Use a slitting machine to slit and reel the film to obtain a finished product.

[0012] Preferably, the oven is a four-stage oven, the temperature of the low temperature zone is 70-90°C, the temperature of the high temperature zone is 110-130°C, and the vehicle speed is 80-120m / min. If the temperature is too low or the time is too short, the reaction is incomplete and the adhesion between the coloring layer and the aluminum-plated layer is insufficient; if the temperature is too high or the time is too long, other components in the colorant may decompose and affect the performance of the coloring layer. The drying temperature and time of the oven in this scheme can better promote this reaction.

[0013] Preferably, the anilox roller has a mesh size of 150-250.

[0014] Compared with the prior art, the present invention has the following beneficial effects: In the hot stamping foil for cloth with heat storage function and the preparation method thereof, a composite film of biaxially oriented polypropylene film and polyethylene film is used as the base layer, and has good moisture resistance, printability, transparency, crispness, strength and elasticity. An aluminum plating layer is provided to improve the overall wear resistance and strength, and the foil has conductivity. The coloring layer uses environmentally friendly dyes, which is more environmentally friendly.

[0015] By optimizing the amount of colorant (polyurethane resin, antistatic agent, etc.), the type of resin binder, and the production process (oven drying temperature and time), the adhesive force, antistatic performance, and heat storage performance of the hot stamping foil for heat storage functional fabrics are comprehensively improved. This comprehensive performance improvement enables the product to better meet the diverse needs of the modern market, whether in daily clothing decoration, warm products, or in application scenarios related to electronic devices.

[0016] Compared with the prior art, the present invention can improve product quality and performance, extend product life, and reduce production costs (for example, by reducing rework or scrap rates due to poor performance). It also helps to enhance product market competitiveness and promote technological progress in related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the overall structure of Example 1 of the present invention.

[0018] The meaning of each number in the figure is: 1. Base layer; 2. Release layer; 3. Aluminum coating layer; 4. Coloring layer; 5. Glue coating layer. DETAILED DESCRIPTION

[0019] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0020] Example 1 according to Figure 1 As shown, an embodiment of the present invention provides a hot stamping foil for cloth with a heat storage function, comprising a base layer 1, a release layer 2 is arranged on the top surface of the base layer 1, an aluminum-plated layer 3 is arranged on the top surface of the release layer 2, a coloring layer 4 is arranged on the top surface of the aluminum-plated layer 3, and the top surface of the coloring layer 4 is covered with a glue coating layer 5.

[0021] On the basis of the above: The base layer 1 is a composite layer of biaxially stretched polypropylene film and polyethylene film, and a nanofiber layer (polylactic acid nanofiber) is added on the basis of the composite layer of biaxially stretched polyethylene film and polyethylene film.

[0022] The adhesive layer 5 is made of resin adhesive, and the resin adhesive is acrylic resin adhesive.

[0023] The coloring layer 4 includes the following components in parts by weight: 5 parts of environmentally friendly dyes, 10 parts of organic solvents, 10 parts of polyurethane resins, and 1 part of accelerators; The metal atoms on the surface of the aluminum atoms on the surface of the aluminum-plated layer 3 and the molecules of the polyurethane resin in the colorant can attract each other through van der Waals force (van der Waals force is caused by instantaneous dipole attraction. Although its strength is weak, it still plays an important role in the close distance between molecules), thereby enhancing the bonding force between the two layers. This force accumulates between a large number of molecules and can form a strong physical adsorption force, which helps to establish a stable interface between the aluminum-plated layer 3 and the coloring layer 4. Secondly, hydrogen bonds can be formed between the amino group (-NH2), carbonyl group (-CO-) in the polyurethane resin and the unshared electron pairs on the surface of the aluminum atoms. The formation of this hydrogen bond can not only enhance physical adsorption, but also strengthen the bonding force between the two layers at the chemical level, so that the coloring layer 4 is more firmly attached to the aluminum-plated layer 3.

[0024] When the polyurethane resin in the coloring layer 4 and the acrylic resin in the coating layer 5 are in contact, their respective molecular chains become entangled. This physical phenomenon increases the degree of entanglement between the molecules and forms a complex network structure. This structure enhances the mechanical locking between the two layers of materials, improves the overall bonding force, and makes the bond between the coloring layer 4 and the coating layer 5 stronger. This interaction is similar to ropes intertwined, which increases the friction between molecules and thus improves the overall bonding strength. In addition to the entanglement of chain segments, intermolecular forces (such as van der Waals forces, hydrogen bonds, etc.) also act between the polyurethane resin and the acrylic resin. Although these forces are weak, they are superimposed on the molecular scale and can significantly enhance the bonding force between the two layers, further consolidating the stability of the entire structure.

[0025] The promoter uses an organic tin promoter (dibutyltin dilaurate). The dibutyltin dilaurate molecule contains tin atoms. The tin atoms have empty d orbitals and can accept electron pairs to form coordination compounds. In the colorant system, they can coordinate with active groups in the polyurethane resin (such as carbonyl oxygen atoms, amino nitrogen atoms, etc.). This coordination changes the electron cloud distribution of the polyurethane resin molecules, making the originally relatively inert chemical bonds (such as bonds related to reaction activity) more active. For example, the carbon-nitrogen bonds adjacent to the amino groups in the polyurethane resin are more easily broken, thereby producing free radicals or ionic intermediates with higher reactivity, which are more likely to react with the aluminum surface.

[0026] The organic solvent used was butanone.

[0027] The environmentally friendly dye comprises the following components in parts by weight: 15 parts of acrylic resin, 1 part of cellulose acetate resin, 10 parts of natural plant pigment, 50 parts of methyl isobutyl ketone, 1 part of antistatic agent, 1 part of wax powder, and 1 part of sodium carbonate; The antistatic agent is a polyethylene glycol type antistatic agent, which plays a role in reducing the electrostatic effect in the coloring layer 4. Static electricity may cause repulsion between molecules, affecting the bonding effect. The polyethylene glycol type antistatic agent reduces this repulsion by adjusting the electrostatic environment between molecules, making it easier for molecules to approach each other, thereby enhancing the bonding effect. The polyethylene glycol type antistatic agent can also help the polyurethane resin and the acrylic resin to better penetrate each other by increasing local wettability, forming a more uniform interface, and improving the overall bonding force.

[0028] From the above, it can be seen that the physical adsorption and chemical bonding between the aluminum layer 3 and the coloring layer 4, the coloring layer 4 and the rubber layer 5, as well as the segment entanglement and intermolecular force between the polyurethane resin and the acrylic resin, all enhance the bonding force between the layers at the molecular level. At the same time, the antistatic agent plays a positive role in reducing the static effect and improving the uniformity of bonding. These interactions and mechanisms work together to build a strong and stable hot stamping foil structure, improving its overall performance and service life.

[0029] A method for preparing a hot stamping foil for fabric with a heat storage function in this embodiment comprises the following steps: S1, selecting a composite film of biaxially oriented polypropylene film and polyethylene film as the base layer 1, coating a release agent on the surface of the base layer 1, and then sending it into an oven for drying and consolidation to form a release layer 2; S2, in a vacuum environment (vacuum degree: 1×10 -3 -1×10 -4 Pa) heating the evaporation boat to 1500°C, continuously feeding high-purity (99.999% purity) aluminum wire into the evaporation boat, causing it to undergo a sublimation reaction to form aluminum vapor, which then evenly adheres to the surface of the release layer 2 to form an aluminum-plated layer 3; S3, putting environmentally friendly dyes, organic solvents, polyurethane resins, and accelerators into a stirring kettle, mixing and stirring to obtain a colorant, using a 150-mesh anilox roller to coat the colorant on the surface of the aluminum-plated layer 3, and then sending it into an oven for drying and consolidation to obtain a colored layer 4; S4, coating the resin binder onto the surface of the coloring layer 4 by an anilox roller, and then sending it into an oven for drying to obtain a coating layer 5; the oven used is a four-stage oven, the temperature of the low temperature zone is 70°C, the temperature of the high temperature zone is 110°C, and the vehicle speed is 80m / min; S5. Use a slitting machine to slit and reel the film to obtain a finished product.

[0030] Example 2 The difference between this embodiment and embodiment 1 is that: The colorant includes the following components in parts by weight: 7 parts of environmentally friendly dye, 15 parts of organic solvent, 13 parts of polyurethane resin and 2 parts of accelerator.

[0031] The organic solvent used was cyclohexanone.

[0032] The environmentally friendly dye comprises the following components in parts by weight: 18 parts of acrylic resin, 2 parts of cellulose acetate resin, 15 parts of natural plant pigment, 60 parts of methyl isobutyl ketone, 3 parts of antistatic agent, 2 parts of wax powder and 2 parts of sodium carbonate.

[0033] The oven adopts a four-stage oven, the temperature of the low temperature zone is 80°C, the temperature of the high temperature zone is 120°C, the speed is 100m / min; the anilox roller is 200 mesh.

[0034] Example 3 The difference between this embodiment and embodiment 1 is that: The colorant comprises the following components in parts by weight: 10 parts of environmentally friendly dye, 20 parts of organic solvent, 15 parts of polyurethane resin and 3 parts of accelerator.

[0035] The organic solvent used was ethyl acetate.

[0036] The environmentally friendly dye comprises the following components in parts by weight: 20 parts of acrylic resin, 3 parts of cellulose acetate resin, 20 parts of natural plant pigment, 70 parts of methyl isobutyl ketone, 5 parts of antistatic agent, 3 parts of wax powder and 3 parts of sodium carbonate.

[0037] The oven adopts a four-stage oven, with the temperature of the low temperature zone being 90°C, the temperature of the high temperature zone being 130°C, the speed being 120m / min; the anilox roller is 250 mesh.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is: The colorant comprises the following components in parts by weight: 5 parts of environmentally friendly dyes, 10 parts of organic solvents, 8 parts of polyurethane resins, and 1 part of accelerator.

[0039] The organic solvent used was butanone.

[0040] The environmentally friendly dye comprises the following components in parts by weight: 13 parts of acrylic resin, 1 part of cellulose acetate resin, 10 parts of natural plant pigments, 50 parts of methyl isobutyl ketone, 1 part of antistatic agent, 1 part of wax powder and 1 part of sodium carbonate.

[0041] Comparative Example 2 The difference between this comparative example and Example 3 is that: The colorant comprises the following components in parts by weight: 10 parts of environmentally friendly dye, 20 parts of organic solvent, 17 parts of polyurethane resin, and 3 parts of accelerator.

[0042] The organic solvent used was ethyl acetate.

[0043] The environmentally friendly dye comprises the following components in parts by weight: 22 parts of acrylic resin, 3 parts of cellulose acetate resin, 20 parts of natural plant pigment, 70 parts of methyl isobutyl ketone, 5 parts of antistatic agent, 3 parts of wax powder and 3 parts of sodium carbonate.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is: The oven adopts a four-stage oven, with the temperature of the low temperature zone being 60°C, the temperature of the high temperature zone being 100°C, and the speed being 70m / min.

[0045] Comparative Example 4 The difference between this comparative example and Example 3 is that: The oven adopts a four-stage oven, with the temperature of the low temperature zone being 100°C, the temperature of the high temperature zone being 140°C, and the vehicle speed being 130m / min.

[0046] Comparative Example 5 The difference between this comparative example and Example 1 is: The colorant comprises the following components in parts by weight: 5 parts of environmentally friendly dyes, 10 parts of organic solvents, 10 parts of polyester resins, and 1 part of accelerators.

[0047] Comparative Example 6 The difference between this comparative example and Example 1 is: The adhesive layer 5 is made of a resin adhesive, and the resin adhesive is a silicone resin adhesive.

[0048] Comparative Example 7 The difference between this comparative example and Example 1 is: The environmentally friendly dye comprises the following components in parts by weight: 15 parts of acrylic resin, 1 part of cellulose acetate resin, 10 parts of natural plant pigment, 50 parts of methyl isobutyl ketone, 1 part of antistatic agent, 1 part of wax powder, and 1 part of sodium carbonate; The antistatic agent uses a carbon nanotube antistatic agent.

[0049] Test example This test example conducts performance test comparison tests on the above-mentioned embodiments 1-3 and comparative examples 1-7.

[0050] 1. Purpose of the test: The comparative tests of Examples 1-3 and Comparative Examples 1-7 demonstrate the advantages of polyurethane resin, acrylic resin binder, polyethylene glycol antistatic agent, and oven drying temperature and time setting in the hot stamping foil for heat storage functional fabrics.

[0051] 2. Test samples: Examples 1-3 are hot stamping foil samples for heat storage functional fabrics prepared according to their respective formulas and processes, and Comparative Examples 1-7 are hot stamping foil samples prepared according to their respective differences from the examples.

[0052] 3. Test equipment: Universal material testing machine: used to test the adhesion between layers and the softness of hot stamping foil; Static potential meter: measure antistatic performance; Heat flow meter thermal conductivity tester: to test the heat storage performance of hot stamping foil.

[0053] 4. Test methods 1. Adhesion test: Test principle: The universal material testing machine measures the bonding force between different layers through a tensile test. The greater the bonding force, the stronger the bond between the layers.

[0054] Steps: Cut out standard size (e.g., 10 mm × 50 mm) strips from the samples of the embodiment and the comparative example, respectively. The strips should include structures such as an aluminum coating layer, a coloring layer, and a rubber coating layer; Fix one end of the sample to the upper fixture of the universal material testing machine and the other end to the lower fixture. Set the tensile speed to 10mm / min, perform the tensile test, and record the maximum tensile force when the sample breaks as the bonding strength measurement result. Repeat the test 5 times for each sample and take the average value.

[0055] 2. Antistatic performance test: Test principle: The electrostatic potential meter measures the electrostatic potential on the surface of the sample. The lower the electrostatic potential, the better the antistatic performance.

[0056] Steps: The samples of the embodiment and the comparative example were placed on the test bench of the electrostatic potential meter and tested in an environment with a temperature of 23±2°C and a relative humidity of 50±5%; Use a friction cloth (wool cloth) to rub the sample surface 10 times at a certain pressure (5N) and speed (10cm / s), and then immediately measure the electrostatic potential of the sample surface. Repeat the test 3 times for each sample and take the average value.

[0057] 3. Thermal storage performance test: Test principle: The heat flow meter thermal conductivity tester measures the thermal conductivity of the sample. Low thermal conductivity ensures that heat is not easily dissipated quickly. The lower the thermal conductivity, the better the heat storage performance.

[0058] Steps: The samples of the embodiments and comparative examples were cut into circular pieces with a diameter of 100 mm; Place the sample into the heat flow meter thermal conductivity tester, test it in a stable test environment (temperature is 25°C), and record the thermal conductivity value. Repeat the test 3 times for each sample and take the average value.

[0059] V. Test results and analysis Table 1 Adhesion test results Sample type Number of tests Average bonding strength (N) Example 1 5 12.82 Example 2 5 13.58 Example 3 5 14.22 Comparative Example 1 5 11.28 Comparative Example 2 5 13.22 Comparative Example 5 5 10.52 Comparative Example 6 5 11.7 As shown in Table 1, from Example 1 to Example 3, as the content of polyurethane resin in the coloring layer increases, the average bonding force increases from 12.82N to 14.22N, which shows that the increase in the content of polyurethane resin helps to improve the bonding force between the layers; in Comparative Example 1, since the polyurethane resin content (8 parts) is lower than that in Example 1, its average bonding force of 11.28N is lower than that in Example 1; although the polyurethane content (17 parts) in Comparative Example 2 is higher than that in Example 3, its average bonding force of 13.22 is lower than that in Example 3. Therefore, it can be explained that within the dosage range provided in this scheme, the bonding force is positively correlated with the dosage of the key component, and Example 3 achieves better bonding force data within this range.

[0060] Secondly, after using polyester resin instead of polyurethane resin in comparative example 5, the average bonding force is 10.52N, which is much lower than 12.82N in example 1. The surface polyurethane resin has a unique advantage in enhancing bonding force. After using silicone resin adhesive instead of acrylic resin adhesive in comparative example 6, the average bonding force of 11.7N is lower than that in example 1, indicating that acrylic resin adhesive has a positive effect on improving bonding force.

[0061] Table 2 Antistatic performance test results Sample type Number of tests Average electrostatic potential (V) Example 1 3 245 Example 2 3 217.67 Example 3 3 200 Comparative Example 7 3 295 As shown in Table 2, in Examples 1-3, as the content of the antistatic agent increases, the average electrostatic potential gradually decreases, which indicates that the increase in the content of the polyethylene glycol antistatic agent can effectively reduce the electrostatic potential and improve the antistatic performance. In Comparative Example 7, after the carbon nanotube antistatic agent is used instead of the polyethylene glycol antistatic agent, the average electrostatic potential is 295V, which is higher than that of Example 1, indicating that the polyethylene glycol antistatic agent has a better antistatic effect in this system.

[0062] Table 3 Thermal storage performance test results Sample type Number of tests Average thermal conductivity (W / (m·K)) Example 1 3 0.0827 Example 2 3 0.0763 Example 3 3 0.0717 Comparative Example 3 3 0.0933 Comparative Example 4 3 0.097 As shown in Table 3, in Examples 1-3, with the reasonable adjustment of the oven drying temperature and time (such as the speed from 80m / min to 120m / min, the temperature of the low temperature zone and the high temperature zone gradually increased), the average thermal conductivity gradually decreased from 0.0827W / (m·K) in Example 1 to 0.0717W / (m·K) in Example 3, indicating that suitable drying conditions are helpful to reduce the thermal conductivity and improve the thermal storage performance. In Comparative Example 3, due to the use of a lower temperature and a slower speed in the oven, its average thermal conductivity of 0.0933W / (m·K) is higher than that of Example 1. In Comparative Example 4, a higher temperature and a faster speed are used, and the average thermal conductivity of 0.097W / (m·K) is also higher than that of Example 1, indicating that the oven drying temperature and time setting range not provided in this case will lead to an increase in thermal conductivity and a decrease in thermal storage performance.

[0063] In summary, polyurethane resin, acrylic resin binder, polyethylene glycol antistatic agent and appropriate oven drying temperature and time setting have an important influence on the performance of hot stamping foil for heat storage functional fabrics. These factors are interrelated and work together on the adhesion, antistatic properties and heat storage properties of the hot stamping foil. For example, good adhesion helps maintain the stability of the hot stamping foil structure, thereby affecting the heat storage performance to a certain extent; the improvement of antistatic properties is also conducive to the stability and reliability of the hot stamping foil in practical applications, which complements other properties.

[0064] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A hot stamping foil for fabric with heat storage function, characterized in that: It comprises a base layer (1), the top surface of the base layer (1) is provided with a release layer (2), the top surface of the release layer (2) is provided with an aluminum coating layer (3), the top surface of the aluminum coating layer (3) is provided with a coloring layer (4), and the top surface of the coloring layer (4) is covered with a glue coating layer (5); The adhesive layer (5) is made of a resin adhesive, and the resin adhesive is an acrylic resin adhesive; The coloring layer (4) is obtained by drying a colorant, wherein the colorant comprises the following components in parts by weight: 5-10 parts of environmentally friendly dyes, 10-20 parts of organic solvents, 10-15 parts of polyurethane resins, 1-3 parts of accelerators, The colorant is prepared by mixing and stirring an environmentally friendly dye, an organic solvent, a polyurethane resin and an accelerator in a stirring kettle; The environmentally friendly dye comprises the following components in parts by weight: 15-20 parts of acrylic resin, 1-3 parts of cellulose acetate resin, 10-20 parts of natural plant pigment, 50-70 parts of methyl isobutyl ketone, 1-5 parts of antistatic agent, 1-3 parts of wax powder, 1-3 parts of sodium carbonate.

2. The hot stamping foil for fabric with heat storage function according to claim 1, characterized in that: The accelerator is an organic tin accelerator, and the organic tin accelerator is dibutyltin dilaurate.

3. The hot stamping foil for fabric with heat storage function according to claim 1, characterized in that: The antistatic agent is a polyethylene glycol type antistatic agent.

4. The hot stamping foil for fabric with heat storage function according to claim 1, characterized in that: The base layer (1) is a composite layer of biaxially oriented polypropylene film and polyethylene film.

5. The hot stamping foil for fabric with heat storage function according to claim 4, characterized in that: The base layer (1) is based on a biaxially oriented polyethylene film and a polyethylene film composite layer, and has an additional nanofiber layer, wherein the nanofiber layer is made of polylactic acid nanofibers.

6. The hot stamping foil for fabric with heat storage function according to claim 1, characterized in that: The organic solvent is one or more combinations of butanone, cyclohexanone and ethyl ester.

7. A method for preparing a hot stamping foil for fabric with heat storage function as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1, coating a release agent on the surface of the base layer (1), and then placing the base layer (1) into an oven for drying and consolidation to form a release layer (2); S2, heating the evaporation boat to 1500° C. in a vacuum environment, continuously feeding high-purity aluminum wire into the evaporation boat, causing it to undergo a sublimation reaction to form aluminum vapor, which then evenly adheres to the surface of the release layer (2) to form an aluminum-plated layer (3); S3, using an anilox roller to coat a colorant on the surface of the aluminum-plated layer (3), and then sending the colorant into an oven for drying and solidification to obtain a colored layer (4); S4, coating the resin binder onto the surface of the coloring layer (4) by means of an anilox roller, and then sending the colored layer into an oven for drying to obtain a coating layer (5); S5. Use a slitting machine to slit and reel the film to obtain a hot stamping foil for cloth with a heat storage function.

8. The method for preparing the hot stamping foil for fabric with heat storage function according to claim 7, characterized in that: In S2, the vacuum degree of the vacuum environment is 1×10 -3 -1×10 -4 Pa, the purity of aluminum wire is 99.999%.

9. The method for preparing the hot stamping foil for fabric with heat storage function according to claim 7, characterized in that: The oven is a four-stage oven, the temperature of the low temperature zone is 70-90°C, the temperature of the high temperature zone is 110-130°C, and the vehicle speed is 80-120m / min.

10. The method for preparing the hot stamping foil for fabric with heat storage function according to claim 7, characterized in that: The mesh size of the anilox roller is 150-250.

Citation Information

Patent Citations

  • Functional heat transfer membrane and preparation method thereof

    CN105751721A

  • Environment-friendly printing ink and preparation method thereof

    CN107304317A

  • Creasing and folding resistance hot stamping foil for leather and preparation method thereof

    CN108859564A

  • Recyclable environment-friendly gluing-free thermal transfer printing ink

    CN109796807A

  • Washable anti-counterfeiting hot stamping film and preparation method thereof

    CN114407547A